2014
DOI: 10.1038/bjc.2014.153
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-initiating capacity is independent of epithelial–mesenchymal transition status in breast cancer cell lines

Abstract: Background:Epithelial–mesenchymal transition (EMT) and cancer stem cells (CSCs) are considered to be crucial for cancer biology. The purpose of this study was to determine whether EMT directly led to the acquisition of tumour-initiating capacity in breast cancer cell lines.Methods:Epithelial–mesenchymal transition was induced in five breast cancer cell lines and one normal breast cell line by EMT-related cytokine stimulation. Mesenchymal–epithelial transition (MET) was induced by stably overexpressing miR-200c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 57 publications
6
23
0
Order By: Relevance
“…Since increased migration is considered a feature of EMT49, we determined if the loss of WT1 also affects the epithelial/mesenchymal balance of breast cancer cells and analysed the RNA levels of several EMT drivers ( SNAI1, SNAI2, ZEB1, ZEB2, TWIST1 ), epithelial markers ( CTNNA1, CTNNA2, CTNND1, CDH1, KRT18 ) and mesenchymal markers ( VIM, TNC, TGFB1, CDH2, MMP2, MMP9 ) through quantitative real-time PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Since increased migration is considered a feature of EMT49, we determined if the loss of WT1 also affects the epithelial/mesenchymal balance of breast cancer cells and analysed the RNA levels of several EMT drivers ( SNAI1, SNAI2, ZEB1, ZEB2, TWIST1 ), epithelial markers ( CTNNA1, CTNNA2, CTNND1, CDH1, KRT18 ) and mesenchymal markers ( VIM, TNC, TGFB1, CDH2, MMP2, MMP9 ) through quantitative real-time PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies of the relationship between the lineage transition and the tumor initiating capability indicated that induction of EMT in breast cancer cells is not associated with enhancing tumor‐initiating capacity, but instead, conferred a CD44 + /CD24 − phenotype and the malignant properties, including cell proliferation, migration, and resistance to chemotherapy and radiation. On the other hand, MET does not lead to inhibition or loss of the tumor‐initiating capacity, but markedly attenuated other malignant properties (Xie et al, ). Repression of the EMT inducer Prrx1 reverted the cells to the epithelial phenotype concomitant with the acquisition of the stem cell properties (Ocana et al, ).…”
Section: Distinct Story Of Relationship Between Emt/met and Pluripotementioning
confidence: 99%
“…Other studies indicate that the CSC or tumor initiating cell (TIC) populations exhibit a hybrid phenotype (55). Clearly, TIC capacity can exist within an epithelial phenotype (56, 57). Barriere and colleagues have suggested the following CSC markers to identify stem-like cells in the blood, regardless of whether they are epithelial or mesenchymal: Aldehyde dehydrogenase-1 (ALDH1), CD44, Gangliosides (GD2, GD3 and GD1a), and ATP-binding cassette transporters (ABC extrusion pump proteins) (58).…”
Section: Emt and Metastasismentioning
confidence: 99%